Counting Footsteps with a Pedometer to Improve HMW Adiponectin and Metabolic Syndrome among Young Female Adults in the United Arab Emirates - Hayder Hasan; Amita Attlee; Hamid Jan Bin Jan Mohamed; Norliyana Aris; Wan Abdul Manan Bin Wan Muda (Hindawi Limited, 2018)
Introduction. Physical activity (PA) may improve cardiometabolic fitness and increase high-molecular-weight adiponectin (HMW-Adip). The pedometer is an effective, user-friendly device to monitor PA with the aim of improving health. This study examined how counting footsteps, using a pedometer, might affect HMW-Adip and MetS components among young females. Methods. Fifty-two females (21.43 ± 4.8 years) were divided into "normal" (BMI = 18-24.9 kg/m2) and "high" (BMI ≥ 25 kg/m2) BMI groups. Participants wore pedometers throughout the day for nine weeks. Pre-post intervention tests performed on anthropometric, biochemical, and nutrient intake variables were tested at p≤0.05. Results. Participants walked 7056 ± 1570 footsteps/day without a significant difference between normal (7488.49 ± 1098) and high (6739.18 ± 1793) BMI groups. After week 9, the normal BMI group improved significantly in BMI, body fat mass (BFM), and waist-hip ratio (WHR). Additionally, percent body fat, waist circumference (WC), and visceral fat area also reduced significantly in the high BMI group. A significant decrease in triglycerides (TG) (71.62 ± 29.22 vs. 62.50 ± 29.16 mg/dl, p=0.003) and insulin (21.7 ± 8.33 µU/l vs. 18.64 ± 8.25 µU/l, p=0.046) and increase in HMW-Adip (3.77 ± 0.46 vs. 3.80 ± 0.44 μg/ml, p=0.034) were recorded in the high BMI group. All participants exhibited significant inverse correlations between daily footsteps and BMI (r=−0.33,  p=0.017), BFM (r=−0.29,  p=0.037), WHR (r=−0.401,  p=0.003), and MetS score (r=−0.49,  p<0.001) and positive correlation with HMW-Adip (r=0.331,  p=0.017). A positive correlation with systolic (r=0.46,  p=0.011) and diastolic (r=0.39,  p=0.031) blood pressures and inverse correlation with the MetS score (r=−0.5,  p=0.005) were evident in the high BMI group. Conclusion. Counting footsteps using a pedometer is effective in improving MetS components (obesity, TG) and increasing HMW-Adip levels.